CORPORATE CRIMINAL LIABILITY IN TAX CRIMES IN INDONESIA: CORPORATE CRIMINAL LIABILITY IN TAX CRIMES IN INDONESIA - Sujatmiko, Sujatmiko; Surono, Agus; Rangsimanop, Pattharawadee (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
The complexity of business structures and the potential for tax avoidance through fictitious schemes contribute to the challenges associated with corporate tax compliance in Indonesia's self-assessment system. This study analyzes the general provisions and procedures of taxation (Tax Administration Law) and the new Criminal Code (KUHP) to understand how corporations are held accountable for tax crimes. The primary concerns pertain to the ambiguity of attributing culpability (mens rea) to non-human entities, the potential for overcriminalization of small corporations, and conflicts of interest within the Directorate General of Taxes (DJP), which fulfills a dual role as both investigator and fiscal authority. A normative legal methodology employing a legislative, conceptual, and historical approach was applied to examine the formulation of articles, corporate liability doctrines, and enforcement mechanisms through the HPP Law, the new KUHP, Supreme Court Regulation No. 13/2016, and Minister of Finance Regulation No. 17/2025. The analysis demonstrates that the legal framework has recognized corporations as criminal subjects through the doctrines of vicarious liability and identification theory, accompanied by penalties ranging from fines to dissolution. Nevertheless, the incentives for compliance mitigation remain limited. The principles of subsidiarity and restorative justice are regulated through voluntary disclosure and alternative penalties. However, implementation requires independent oversight to maintain checks and balances. The recommendations put forth include refining the definition of